Associations between semantic memory for proper names in story recall and CSF amyloid and tau in a cognitively unimpaired sample. (20th December 2022) - Hale, Madeline R; Koscik, Rebecca Langhough; Du, Lianlian; Hermann, Bruce P; Van Hulle, Carol A.; Suridjan, Ivonne; Kollmorgen, Gwendlyn; Basche, Kristin E; Bruno, Davide; Sanson‐Miles, Leah; Jonaitis, Erin M.; Chin, Nathaniel A.; et al.
Abstract: Background: Difficulty recalling proper names (PNs; e.g., names of people/places) is a common complaint of individuals at risk for Alzheimer's disease (AD). We recently reported that cognitively unimpaired (CU), positron emission tomography amyloid‐beta (Aβ) positive (A+) individuals recalled fewer PNs than Aβ negative individuals on the Logical Memory (LM) delayed story recall test. Declines in delayed LM total scores (LMtot) have been associated with cerebrospinal fluid (CSF) A+ and tau (T); the relationship between PNs and AD‐CSF biomarkers is unknown. We investigated whether delayed recall of PNs at baseline, or most recent visit, were associated with biomarker positivity for two AD‐CSF biomarkers, and whether PNs were more strongly associated than traditionally used LMtot scores. Method: CU participants with no other neurological diagnoses and CSF data available were included from the Wisconsin Registry for Alzheimer's Prevention (N = 219; mean baseline age [standard deviation] = 58.12 [6.31]). Item‐level LM data were used to create PNs (0–9) and LMtot (0–50) scores. A and T statuses (+/‐) were determined using published cutoffs for CSF Aβ42/40 and phosphorylated tau 181 (pTau181 ). Logistic regression models investigated whether LMtot or PNs were associated with most recent biomarker status, covarying CSF age, sex, Wide Range Achievement Test‐3 score, and apolipoprotein E4 status. Model fits were compared using Akaike information criterion (AIC). For descriptive purposes, effect sizes between adjusted means of PNs and LMtot were calculated for biomarker‐positive vs. negative groups. Result: Overall, 31 individuals (14%) were Aβ42/40 + and 29 (13.0%) were pTau181 + (Table 1 ). Baseline PNs nor LMtot were not significantly associated with AD‐CSF biomarkers (Table 2 ). Most recent PNs and LMtot were associated with AD‐CSF (Table 3 ). AICs indicated similar fits between PNs and LMtot at each timepoint, and better fits with most recent vs. baseline LM scores. Effect sizes were higher for most recent LM metrics compared to baseline and were slightly higher for PNs than LMTot for Aβ (Figure 1 ). Conclusion: Metrics from story recall tasks are associated with increased risk of CSF‐AD biomarker positivity and suggest that PNs from story recall may be sensitive to early AD biomarker changes. Validation by replication in additional cohorts is required.